1999
DOI: 10.1111/1469-7610.00433
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Processing among High‐functioning Persons with Autism

Abstract: Two tasks were used to assess the processing of whole versus parts of objects in a group of high-functioning children and adolescents with autism (N = 11) and a comparison group of typically developing peers (N = 11) matched for chronological age and IQ. In the first task, only the children with autism showed a global advantage, and the two groups showed similar interference between levels. In the second task, the children with autism, despite longer RTs, showed similar performance to the comparison group with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
4
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(68 citation statements)
references
References 38 publications
9
54
4
1
Order By: Relevance
“…In this theory, the local advantage does not necessarily imply a complete disruption of configural or global processes. Indeed, the typical global-to-local visual processing order has been found in perceptual tasks with high-functioning adolescents (Mottron et al, 1999) and with high-and low-functioning children (Deruelle, Rondan, Gepner, & Fagot, 2006;Ozonoff, Strayer, McMahon, & Filloux, 1994) with ASD. Despite empirical evidence of intact global processing abilities, individuals with ASD reliably demonstrate an automatic reliance on the local information in static visual stimuli (Mottron et al, 2006).…”
Section: Comparisons Of Visual Motion Processingmentioning
confidence: 96%
See 1 more Smart Citation
“…In this theory, the local advantage does not necessarily imply a complete disruption of configural or global processes. Indeed, the typical global-to-local visual processing order has been found in perceptual tasks with high-functioning adolescents (Mottron et al, 1999) and with high-and low-functioning children (Deruelle, Rondan, Gepner, & Fagot, 2006;Ozonoff, Strayer, McMahon, & Filloux, 1994) with ASD. Despite empirical evidence of intact global processing abilities, individuals with ASD reliably demonstrate an automatic reliance on the local information in static visual stimuli (Mottron et al, 2006).…”
Section: Comparisons Of Visual Motion Processingmentioning
confidence: 96%
“…As a result, typical observers are hindered, relative to observers with ASD, in their detection of embedded figures. Other examples of a local processing advantage in ASD include superior performance on the block design task (Shah & Frith, 1993), the reproduction of impossible figures (Mottron, Burack, Stauder, & Robaey, 1999), visual search (O'Riordan, Plaisted, Driver, & Baron-Cohen, 2001;Plaisted, O'Riordan, & Baron-Cohen, 1998b), the ability to learn highly confusable patterns (Plaisted, O'Riordan, & Baron-Cohen, 1998a), and performance on tasks with Navon figures that are incongruent across local and global levels of analysis (Wang, Mottron, Peng, Berthiaume, & Dawson, 2007). Although observers with ASD are capable of processing visual information globally, their default perceptual setting is to process static images at the local level (Behrmann et al, 2006;Happé & Frith, 2006;Mottron et al, 2006).…”
Section: Comparisons Of Visual Motion Processingmentioning
confidence: 99%
“…In vision, Bertone et al (2003) found that individuals with ASC are more accurate at detecting the orientation of firstorder gratings (simple, luminance-defined) but less accurate at identifying second-order gratings (complex, texture-defined). In the auditory modality, superior pitch processing has been found in ASC (Mottron et al 1999;Bonnel et al 2003;Heaton et al 2008). In a case study, Mottron et al (1999) reported exceptional absolute judgement and production of pitch.…”
Section: Sensory Hypersensitivitymentioning
confidence: 99%
“…In the auditory modality, superior pitch processing has been found in ASC (Mottron et al 1999;Bonnel et al 2003;Heaton et al 2008). In a case study, Mottron et al (1999) reported exceptional absolute judgement and production of pitch. Bonnel et al (2003) In the tactile modality, Blakemore et al (2006) showed hypersensitivity to vibrotactile stimulation to a frequency of 200 Hz but not for 30 Hz.…”
Section: Sensory Hypersensitivitymentioning
confidence: 99%
“…On the other hand, the global structures in such stimuli are usually so simple that they can be discerned easily via conscious pattern recognition. For instance, when explicitly asked for, high-functioning ASD individuals seem well able to correctly report such global structures (Koldewyn et al, 2013;Mottron et al, 1999;Plaisted, Swettenham, & Rees, 1999;Rinehart et al, 2000). Such instructions in fact appeal to (conscious) attention rather than to (nonconscious) perception, and I do not exclude that, by way of an ''optional'' long-term attentional strategy, high-functioning ASD individuals train themselves in conscious pattern recognition to compensate for the fact that -as WCC suggests -they do not perceive global structures as instantaneously as typical individuals do.…”
Section: The Local Advantage Phenomenon In Asdmentioning
confidence: 99%